KODE ETIK DAN TEKANAN PUBLIK MEDIA MASSA - Nuryanti, Nuryanti; Nurkamila, Safrina; Evani, Sheptia; fahreza, Arta; JR, Tri Yutdo (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2023)
This article focuses on the examination of mass media ethics. Mass communication involves the entire spectrum of society with various differences encompassing aspects of religion, education, age, and social status, and involves all that can be reached by mass media. Media serves as a means of communication and a source of information for the community, enabling every narrative and story to be managed and presented through the media whenever needed. Its influence can be both positive and negative for mass media users, whether in the context of communities, organizations, or companies that involve many people or audiences. In social, national, and democratic life, the freedom to express thoughts and opinions aligns with conscience and essential human rights. Governments enact regulations regarding media ethics to ensure that every media user is cautious in expressing and receiving opinions. Thus, through an examination of mass media ethics, a structured media environment can be created, avoiding ethical violations that may have serious consequences for those involved.